PERAN KEPEMIMPINAN KH. ABDULLAH SHIDDIQ DALAM PEMBENTUKKAN KARAKTER SANTRI PONDOK PESANTREN BUSTANUL ULUM GLAGAH LAMONGAN - Aridlah Sendy Robikhah; Riska Dwita Sari (Universitas Islam Lamongan, 2021)
The research entitled Leadership Role of KH. Abdullah Shiddiq in Shaping the Character of Santri Pondok Pesantren Bustanul Ulum Glagah Lamongan. Using this type of qualitative research -phenomenology, the purpose of this study was to determine the role of leadership in shaping the character of students at the Bustanul Ulum Islamic Boarding School Glagah Lamongan. From the results of this study, the first in the form of Kyai Abdullah Siddiq's leadership is very firm, friendly, responsible, disciplined, and able to be an example for everyone. The second is the process of character building at the Bustanul Ulum Islamic Boarding School which is carried out in several ways, such as giving examples, habituation, advice and motivation, supervision, prohibitions or rules, and punishments. Moreover, the last is the leadership role of Kyai Abdullah Shiddiq, which is summarized in three points: an interpersonal role or role model for the community, decision role or Kyai as decision making, and Kyai as an information role or source of information in controlling the lives of students.